Assessment of eHealth behaviors in national surveys: a systematic review of instruments. (23rd October 2018) - Hong, Y Alicia; Cho, Jinmyoung
Abstract: Objectives: To conduct a systematic review of instruments used in national surveys of eHealth behaviors. Materials and Methods: Major databases and websites of federal agencies were searched with pre-determined inclusion and exclusion criteria. National surveys with measures of eHealth behaviors were identified. The survey instruments were retrieved, and their measures of eHealth behaviors were categorized and critiqued. Results: We located 13 national surveys containing eHealth behavior assessment questions that were administered from 1999 to 2017. Most surveys were conducted annually or biennially and typically covered topics on searching health information, obtaining social support, communicating with healthcare providers, and buying medicine online; recent surveys included items related to personal health management and use of mobile tools. There were redundant measures of searching health information online but insufficient measures of use of mobile apps, social media, and wearable devices. Discussion: Future assessment of eHealth behaviors should reflect the growing varieties of behaviors enabled by technology development and reflect the current mobile ownership patterns in diverse social groups. More studies also need to include longitudinal surveys, integrative and standardized measures, and better designs to allow data linkage and comparison. Conclusion: The existing survey instruments covering eHealth behaviors are rather limited compared to fast technological progress. We call for more national surveys on eHealth behaviors that are more responsive to technology development; we also advocate for more analysis and dissemination of existing national data on eHealth behaviors for evidence-based health policies.